The Role of CD44 in Disease Pathophysiology and Targeted Treatment - Jordan, Andre R.; Racine, Ronny R.; Hennig, Martin J. P.; Lokeshwar, Vinata B. (Frontiers in Immunology, 2015)
The cell-surface glycoprotein CD44 is involved in a multitude of important physiological functions including cell proliferation, adhesion, migration, hematopoiesis, and lymphocyte activation. The diverse physiological activity of CD44 is manifested in the pathology of a number of diseases including cancer, arthritis, bacterial and viral infections, interstitial lung disease, vascular disease and wound healing. This diversity in biological activity is conferred by both a variety of distinct CD44 isoforms generated through complex alternative splicing, posttranslational modifications (e.g., N- and O-glycosylation), interactions with a number of different ligands and the abundance and spatial distribution of CD44 on the cell surface. The extracellular matrix glycosaminoglycan hyaluronan (HA) is the principle ligand of CD44. This review focuses both CD44-hyaluronan dependent and independent CD44 signaling and the role of CD44-HA interaction in various pathophysiologies. The review also discusses recent advances in novel treatment strategies that exploit the CD44-HA interaction either for direct targeting or for drug delivery.